Misconceptions of Depression in African Americans - Sohail, Zohaib; Bailey, Rahn Kennedy; Richie, William D. (Frontiers in Psychiatry, 2014)
Major depression is a very common disabling disorder. Although the relationship between race and depression is complex, depression affects all races, all ethnic and geographic locations as well as all age groups. The prevalence of depression in African Americans is controversial, due to the paucity of research. The deficit in the knowledge and skills in treating depression in African Americans have not been adequately addressed so far. Inadequate and insufficient data on African Americans contributes to the problems of under diagnoses, misdiagnosis, and under treatment of depression. This article will highlight the existing problem of depression in Afro American with a focus on diagnostic and treatment issues.